Peningkatan Kualitas Pelayanan Publik Kepariwisataan (Studi Kasus: Obyek Wisata Pangandaran) - Putro, Utomo Sarjono; Rahmana, Arif (Jurnal Manajemen Teknologi, 2003)
As stated in the National Development Program (PROPENAS), in the Strategic Plan (RENSTRA) of West Java and in the Area Program Development (PROPEDA) of Ciamis, tourism should be developed professionally to gain tourist satisfaction. Recently Pangandaran frequently getting criticism from tourists. For example the parking system is not managed regulary, the security system is not well guaranted, the settlement of merchant is not managed well and the environtment looks very dirty. To give a suggest of improvement of Quality of Tourism Public Service, this research use a Quality Function Deployment (QFD) method which is based on the SERVQUAL Model  using quality variables, there are Tangibility, Realibility, Responsiveness, Assurances and Empathy. This research adopt 39 attributes of tourism service which is judged by tourist. The survey result 19 attributes have positive SERVQUAL score so it have satisfied the tourist yet. The value of Customer Satisfaction Indexs (CSI) obtained equal to 94,8%. It’s mean that level service of Pangandaran is not yet really satisfy the tourist. Attributes with negative SERVQUAL score is judged as voice of customer to quality of tourism public service. The improvement of quality of tourism public service are training program, operational activity program,repair or addition of tourism facility program and addition of human resources program. Keywords: SERVQUAL, QFD, Voice of Customer